IDENTITAS DIRI SUPORTER PEREMPUAN SEPAK BOLA TIMNAS INDONESIA (Studi Fenomenologi Mengenai Fanatisme Mahasiswi Fisip Unsika Suporter Sepak Bola Timnas Indonesia) - Adriansyah, Aditya Tri; Utamidewi, Wahyu; Nurkinan, Nurkinan (Innovative: Journal Of Social Science Research, 2025)
This study aims to understand the construction of self-identity of female supporters of the Indonesian National Team, especially among female students of FISIP Unsika. Using Alfred Schutz's phenomenological approach, this study examines the motives, meanings, communication experiences, and interactions of female supporters while watching live matches of the Indonesian National Team at the stadium. The results of the study indicate that the self-identity of female supporters is formed through direct experience, social interaction, and the process of constructing meaning that is closely related to their collective and individual experiences as part of the national football supporter community.